Acute Tryptophan Depletion Moja-De: A Method to Study Central Nervous Serotonin Function in Children and Adolescents - Stewart, Richard M.; Wong, Janice W. Y.; Mahfouda, Simone; Morandini, Hugo A. E.; Rao, Pradeep; Runions, Kevin C.; Zepf, Florian D. (Frontiers in Psychiatry, 2020)
Serotonin (5-HT) is widely implicated as a key neurotransmitter relevant to a range of psychiatric disorders and psychological processes. Serotonergic challenge methodologies provide unparalleled insight into the in vivo role of 5-HT on behavioural, physiological, and neuropsychological processes. Acute tryptophan depletion (ATD) is a key challenge method where by diminished dietary intake of tryptophan – the amino acid precursor to brain 5-HT synthesis – results in temporary diminished central nervous 5-HT synthesis. This protocol outlines the Moja-De ATD neuropharmacological challenge methodology and its benefits over previously used ATD techniques. These modifications enable the use of ATD Moja-De in child and adolescent populations, providing a methodology for interrogating the role of 5-HT in human psychopathology from a developmental viewpoint.